Design and Application for Automatic Train Operation System Based on HXD1 Locomotive - Yong XIAO; Long ZHU; Jun WU; Xin WANG; Jieliang ZHOU; Yongxin LIU (机车电传动)
This paper mainly introduced the design and application of the automatic driving system of the HXD1 type AC drive electric locomotive. Based on the principle of minimizing locomotive alteration and cost, the automatic driving function can be realized by installing automatic driving system equipment, communication and power supply cable. Through the successful application of the locomotive automatic system, the manual labor intensity was reduced, the human error factors were eliminated, and the locomotive operation level and consistency were improved.